Post-Mining Reclamation as An Environmental Policy: A Gold Mining Case Study - Thalib, Prawitra; Kurniawan, Faizal; Aliansa, Wahyu; Maulani, Atiqoh Farhah (Halu Oleo Law Review, 2020)
Gold mining in south-east Sulawesi Bombana is one of the potential natural resources in Indonesia. But nowadays the condition is due to lack of responsibility of the mining business to conduct post-mining reclamation in Bombana area, even though the mining activity has been carrying out mining business license. Post-mining activities are very important and must be done by the mining company, because it can minimize the destruction of natural environment in the mining site. The purpose of this research is to find out the mining conditions in the Bombana area as well as arrangements related to post-mine reclamation in the Bombana area. This study was written using the normative from data obtained by library research. Then related to the implementation of post-mining reclamation in Bombana is currently not carried out maximally, it is due to the uncertainty of regulations related to the post-mine reclamation obligations and the sanctioned rules that will be applied in the future still depend on local government regulations but the implementation is still not able to work effectively. So the steps that need to be taken in this case to avoid damage to the environment surrounding the mining site is necessary cooperation between the Government, the mining business actors and the community using soil conservation technology such as post-mining reclamation, which is regulated in a clear, transparent, accountable legislation.